Monoclonal Antibodies : A Practical Approach - Shepherd, Philip S; Ed. Dean, Christopher; Ed (Practical approach series., 2000)
Monoclonal Antibodies: A Practical Approach deals with the preparation, testing, derivation, and applications of monoclonal antibodies. It will be an invaluable laboratory bench companion to both new and experienced immunologists.